Investigação científica em seres humanos: a experiência de voluntários nos ensaios clínicos de uma nova vacina - Carolina Hespanha Almeida (2009)
This study is about the scientific investigation in human beings. The clinical experiments areresearches in which the biomedical technologies can be tested, creating new discoveries andguaranteeing advances in medicine and in the quality of life of the people. These studies stimulate thedebate about ethics in research, especially when the researches are developed in areas of socialvulnerability. In Brazil, the legislation of 1996 highlights the pertinence and relevance of this subject,since little is known about the participation of people in clinical tests and about which aspects arerelated to the experience of being a volunteer: decision and motivation to participate, perceptions,feelings and attitudes. The SABIN Institute (USA) and the Fundação Oswaldo Cruz are developing anew vaccine against Hookworms in the northeastern countryside of the state of Minas Gerais, Brazil.This is a region with a vulnerable population where the social-economical exclusion may cause thesubjects, even after receiving information about the research, to participate in the study without fullknowledge of the real risks and benefits. For this reason, the Nursing School develops actions toeducate and prepare the community. This study is a part of these actions, and has as an objective toanalyze the experiences of the volunteers in the clinical tests of the vaccine against Hookworms. Thisstudy has a qualitative approach based on the Comprehensive Theories. The subjects are part of theCut 1 Phase 1 of the tests of the new vaccine. Nine people were interviewed. We used, to gatherdata, semi-structured interview with the use of photographic images as a free-association resource. Toanalyze the data, we made the option to use the Content Analysis as the theoretical reference ofAnthropology. The result of the analysis showed many aspects of the experience of being a volunteer:The decision to participate the desire and the certainty to participate, the desire of having the wormconfronted with the desire to participate, the free, spontaneous decision; The community, researchers,relationships and feelings: the dialog, the image and valorization of the researchers, the image of thedoctor and the feelings of trust; The influence of the family and of the community: the support and thenon-participation of the family without influencing the decision, the community, opinions andfeelings, to be a volunteer is to be a courageous man; Tests of the vaccine what to expect: benefitswith the research, health gains, selflessness and benefits to others, hope; Vaccine: beliefs, fantasiesand feelings: the curiosity, religious beliefs; The tests sensations and feelings: pride to participate,happiness, fear; The experience to suffer something: physical pain, side effects and theanthropological models, the tests of the vaccine and daily life; The experience and the perceptions ofthe vaccine: the vaccine as a treatment, new knowledge the vaccine as prevention, the vaccine andthe difficulties of the place. Shortly, the experience of being a volunteer (re)built a path that shows usa predisposition of the people to participate. Such predisposition peaks with the conscientiousdecision that is not imposed by the family, by the community or by the researches. Even if the subjectexpects to receive any health benefits, there is selflessness in contributing to the research of a vaccinethat will improve the health of other people. The study helped us perceive the experience of volunteersin clinical tests and the relevant role of the education actions and the preparation of the community sothat the experience can be positive.